Interfacial interactions and properties of cellular structured polyurethane nanocomposite based on carbonaceous nano‐fillers. Issue 2 (18th September 2020) - Mandal, Subhash; Roy, Debmalya; Prasad, Namburi Eswara; Joshi, Mangala
Abstract: In this article, we have studied the effect of carbonaceous nanofillers viz. fullerenol (0D), carboxylated multi‐wall carbon nanotube (MWCNT, 1D), hydroxylated graphene (2D) and combination of carboxylated CNT and hydroxylated graphene as 3D in thermoplastic polyurethane on the tensile properties of the fabricated cellular structures. The concentration of nano‐fillers was varied as 0.1, 1, and 5 wt%. Tensile properties of the nanocomposite cellular structures were measured as per ASTM D882 at 20°C (below glass transition temperature, T g ) and 40°C (above T g ). The results have shown that the tensile strength was found to increase by 200%–300% and the tensile modulus was found to increase by 150%–300% for 2D and 3D nano‐fillers while significantly poor results were observed for 0D. However, the test data tensile strength and modulus showed marginal increase at 20°C and marginally low at 40°C for 1D filler. The interfacial adhesion was calculated by using experimental tensile data and the predictive models. The interfacial adhesion parameter ( B σ ) calculated using Pukanszky equation was found significantly higher value for 2D ( B σ20 = 195.8) and 3D ( B σ20 = 192.0) fillers while poor adhesion was observed for 0D ( B σ20 = −81.6) fillers. The developed cellular structured materials were also evaluated by attenuated total reflection Fourier transform IR spectra, differential scanning calorimetry, X‐ray diffraction, scanning electron microscope, and transmission electron microscope. Abstract :